Development of the SAKOLA Application: An Android-Based Assessment System for Physical Education, Sports, and Health in Elementary Schools - Rizkiya, Ikhlas; Syamsuar, Syamsuar (Postgraduate School, Universitas Negeri Padang, 2024)
This study aims to develop the SAKOLA (School Administration System) application, an Android-based tool designed to enhance the assessment process in Physical Education, Sports, and Health learning in elementary schools. Employing the Research and Development (R&D) methodology with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the study systematically addressed existing challenges faced by teachers in conducting assessments. Observations in Padang City elementary schools revealed significant difficulties, including manual processes, inadequate facilities, and a lack of technological tools for recording, analyzing, and communicating learning outcomes. The School Administration System (SAKOLA) application was designed to address these issues by providing features such as automatic summarization of assessments, mobile accessibility, and user-friendly navigation. The results demonstrated that the application is highly valid, with expert evaluations yielding an average validity score of 82.86%, categorized as